2010
DOI: 10.1084/jem.20092301
|View full text |Cite
|
Sign up to set email alerts
|

Complement drives Th17 cell differentiation and triggers autoimmune arthritis

Abstract: Activation of serum complement triggers Th17 cell–dependent spontaneous autoimmune disease in an animal model. In genetically autoimmune-prone SKG mice, administration of mannan or β-glucan, both of which activate serum complement, evoked Th17 cell–mediated chronic autoimmune arthritis. C5a, a chief component of complement activation produced via all three complement pathways (i.e., lectin, classical, and alternative), stimulated tissue-resident macrophages, but not dendritic cells, to produce inflammatory cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
166
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(176 citation statements)
references
References 32 publications
8
166
1
1
Order By: Relevance
“…1f). These findings suggest that under arthritic conditions, CD25 lo Foxp3 + CD4 + T cells are prone to differentiate into T H 17 cells that are known to have a key pathological role in arthritis [13][14][15][16][17][18] .…”
Section: Results T H 17 Cells Arise From Cd25 Lo Foxp3 + T Cells In Amentioning
confidence: 93%
“…1f). These findings suggest that under arthritic conditions, CD25 lo Foxp3 + CD4 + T cells are prone to differentiate into T H 17 cells that are known to have a key pathological role in arthritis [13][14][15][16][17][18] .…”
Section: Results T H 17 Cells Arise From Cd25 Lo Foxp3 + T Cells In Amentioning
confidence: 93%
“…We further detected a reduction in a number of T cell receptor (TCR) signaling-related molecules, including CD81, TARP (CD3g), and CD247 (CD3z), and TCR signal strengthmodulating IL-2R (IL2RB) (31). Altered TCR signaling can affect the skewing of T cell polarization and selection, as seen in SKG mice, in which signaling defects associated with CD3z result in an increase in autoreactive T cells, including Th17 cells (32,33). It is thus tempting to hypothesize that altered TCR signaling in AS patients may be affecting T cell polarization and self-reactivity.…”
Section: Discussionmentioning
confidence: 90%
“…A vaccine that induces generation of anti-C5a antibodies has been shown to be effective in murine collagen-induced arthritis (CIA) in mice [16], and oral treatment with a small molecule C5a antagonist reduced joint damage in the rat antigen-induced arthritis model [17]. In several mouse models of arthritis C5aR-deficient mice show reduced disease development [18][19][20][21]. In human C5aR knockin mice, a mouse anti-human C5aR monoclonal antibody effectively ameliorated neutrophil-dependent K/B Â N serum transfer-induced arthritis [22], and it has been shown that antimouse C5aR mAb lowers disease activity when administered in the early stages of murine CIA [23].…”
Section: Introductionmentioning
confidence: 99%